Sarcopenia and Systemic Inflammation Synergistically Impact Survival in Oral Cavity Cancer. (2nd November 2020) - Lee, Jie; Liu, Shih‐Hua; Dai, Kun‐Yao; Huang, Yu‐Ming; Li, Chi‐Jung; Chen, John Chun‐Hao; Leu, Yi‐Shing; Liu, Chung‐Ji; Chen, Yu‐Jen
Abstract : Objectives: Sarcopenia and systemic inflammation can affect survival of advanced‐stage oral squamous cell carcinoma (OSCC) patients; however, their reciprocal associations with survival outcomes are yet to be investigated. Study Design: Retrospective review at a tertiary cancer center. Methods: Patients with stage III‐IVB OSCC that underwent surgery and (chemo)radiotherapy at our institution between 2010 and 2015 were reviewed. Skeletal muscle index (SMI) was assessed using computed tomography scans at the C3 vertebra. Sarcopenia was defined at the lowest sex‐specific tertile for SMI. Systemic inflammation was estimated using the modified Glasgow prognostic score (mGPS), which ranges from 0 to 2 based on serum C‐reactive protein and albumin levels. The predictors of overall survival (OS) were evaluated using Cox regression models. Results: A total of 174 patients were included in the study. The cut‐off values for sarcopenia were set at SMI <52.4 cm 2 /m 2 (men) and < 36.2 cm 2 /m 2 (women) corresponding to the lowest sex‐specific tertile. An mGPS 1–2 was independently associated with sarcopenia (odds ratio: 2.05; 95% confidence interval: 1.06–3.97; P = .03). On multivariate analysis for OS, sarcopenia and mGPS 1–2 independently predicted OS (hazard ratio: 2.12; 95% confidence interval: 1.17–3.85; P = .01 and hazard ratio: 7.85; 95% confidence interval: 3.7–16.65; P  < .001, respectively). Patients with both sarcopenia and mGPS 1–2 (vs. neither) had worse OS (hazard ratio: 16.80; 95% confidence interval: 6.01–46.99; P  < .001). Conclusions: Sarcopenia and systemic inflammation may exert a negative synergistic prognostic impact in advanced‐stage OSCC patients. Level of Evidence: 4 Laryngoscope, 131:E1530–E1538, 2021